CHITOSAN AND ASPERGILLUS NIGER MEDIATED ELICITATION OF TOTAL FLAVONOIDS IN SUSPENSION CULTURE OF ANDROGRAPHIS PANICULATA (BURM.F.) NEES. - V. D. MENDHULKAR; M. M. A. VAKIL (International Journal of Pharma and Bio Sciences, 2013)
Plant Flavonoids are considered as naturally occurring bioactive compounds. In the present study, chitosan and Aspergillus niger elicitors were used as chemical and fungal elicitors, respectively. The cell suspension culture of Andrographis paniculata (Burm. f.) Nees was established in 50 ml MS media supplemented with 2,4-D: BAP (1.0:0.5 mg/l) and treated with chitosan and Aspergillus niger elicitors to enhance the accumulation of total flavonoids under in vitro condition. Quantitative analysis of total flavonoids accumulation was done by aluminum chloride colorimetric method. The results revealed that chitosan treatment with 20 mg for 24 hrs. duration explored highest elicitation of flavonoid i.e. 3.51 mg/g (2.72 fold) compared to control and rest of the treatments. Biological elicitor, Aspergillus niger with 2 ml, 4 days treatment was most promising with induction of 1.39 fold enhancement in flavonoid content (3.37 mg/g) over the control (2.42 mg/g).